Teaching large online and blended classes - Koç, Selma; Boboc, Marius (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"As the interest in online learning continues to grow, many higher education institutions offer large classes online. Such courses may prompt managerial and pedagogical challenges for effective teaching and learning. Most online classes depend on text-based information and communication. While there are advantages to text-based information and asynchronous written assignments and discussions, large online classes may lack student-centered, and active learning environments. In addition, providing timely and effective feedback to the students can be challenging and time-consuming for instructors of large online classes. Instructional strategies that rely on collaborative online tools and mobile applications can help facilitate student engagement and active learning while addressing pedagogical challenges of large online classes. Mobile technologies can facilitate formative assessment and personalized instruction while augmented reality applications can help engage students in authentic learning and the transfer of knowledge and skills to real-life situations (Fritschi & Wolf, 2012). In addition, recent technology tools can provide just-in-time access to resources and shared collaborative spaces for students or teachers to work together on projects. This book aims to provide practical assistance to those who teach large online classes by addressing the following research questions with practical implications for teaching and learning: What teaching and assessment strategies do instructors use to facilitate active learning in large online classes? What strategies do instructors use to reduce instructor and learner cognitive overload? What does research suggest for effective teaching and learning in large online classes? What are suggestions for professional development of instructors who teach large online classes? What are suggestions for orienting students for effective learning in large online classes?"--